2019
DOI: 10.1108/er-04-2017-0091
|View full text |Cite
|
Sign up to set email alerts
|

What matters for knowledge work productivity?

Abstract: Purpose Knowledge work productivity is a well-studied topic in the existing literature, but it has focussed mainly on two things. First, there are many theoretical models lacking empirical research, and second, there is a very specific research regarding how something impacts productivity. The purpose of this paper is to collect empirical data and test the conceptual model of knowledge work productivity in practice. The paper also provides information on how different drivers of knowledge work productivity hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 58 publications
0
31
1
4
Order By: Relevance
“…While leisure satisfaction, a positive feeling derived from leisure activities (Beard and Ragheb, 1980;Kuykendall, Tay and Ng 2015), has received less attention. It is found that both job and leisure satisfaction are related to knowledge workers' job performance and turnover intentions (Allen, Bryant and Vardaman 2010;Palvalin 2019;Yigitcanlar, Baum and Horton 2007). Consequently, employers, particularly those in rapidly growing economies like China, are exploring new tactics for improving satisfaction levels in their knowledge workforce (Fish 2015).…”
Section: Introductionmentioning
confidence: 99%
“…While leisure satisfaction, a positive feeling derived from leisure activities (Beard and Ragheb, 1980;Kuykendall, Tay and Ng 2015), has received less attention. It is found that both job and leisure satisfaction are related to knowledge workers' job performance and turnover intentions (Allen, Bryant and Vardaman 2010;Palvalin 2019;Yigitcanlar, Baum and Horton 2007). Consequently, employers, particularly those in rapidly growing economies like China, are exploring new tactics for improving satisfaction levels in their knowledge workforce (Fish 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Memahami pengetahuan produktivitas kerja dan penggeraknya secara lebih komprehensif telah menjadi masalah yang cukup topikal karena konsep cara kerja yang baru (Palvalin, 2019).…”
Section: Produktivitas Kerjaunclassified
“…Though it may seem obvious that KWs use knowledge, there have been several—often competing—attempts to articulate exactly what this means (Pyöriä, 2005; Palvalin, 2019). It has been used synonymously with “white collar” work (Okkenen, 2004), associated with highly qualified and talented individuals (Costas & Karreman, 2016), and used as a catch‐all term for the future of work.…”
Section: A Research Agendamentioning
confidence: 99%